2017
DOI: 10.3329/jbau.v15i2.35071
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological investigation of gastrointestinal parasites of small ruminants in Tangail, Bangladesh

Abstract: Gastrointestinal (GI) parasitism is anegregious problem in small ruminant production system due to is impact on growth and associated cost of control measures. An epidemiological study was conducted to investigate the prevalence of gastrointestinal parasites of small ruminants from different areas of Madhupur, Tangail. The stool samples were collected from a total of 426 goats and sheep from study areas. Specimens were subjected to Stoll's ova counting technique and the overall prevalence of gastrointestinal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 12 publications
6
25
1
1
Order By: Relevance
“…The overall prevalence of GI parasitic infections was 68.64% in sheep and 61.82% in goats, which indicate a high level of such infections in the study sites. A similar type of prevalence was reported in previously published reports (Asif et al 2008;Rahman et al 2017). However, the overall prevalence reported in this investigation was relatively lower than the findings of prior reports who reported 79-86% in sheep and 89-90% in goats of Noakhali district, Bangladesh and Punjab, India (Singh et al, 2017;Hossain et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The overall prevalence of GI parasitic infections was 68.64% in sheep and 61.82% in goats, which indicate a high level of such infections in the study sites. A similar type of prevalence was reported in previously published reports (Asif et al 2008;Rahman et al 2017). However, the overall prevalence reported in this investigation was relatively lower than the findings of prior reports who reported 79-86% in sheep and 89-90% in goats of Noakhali district, Bangladesh and Punjab, India (Singh et al, 2017;Hossain et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…This study further showed a lack of significant difference in the overall occurrence of GI parasitic infections between the study animals. This might be due to rearing of both sheep and goats together giving them a higher chance to be infected with those species of parasites through crosscontamination (Rahman et al 2017). The species of GI parasites identified in the current investigation have also been reported in various places in Bangladesh (Hossain et al 2015;Rahman et al 2017).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies from Bangladesh on domestic sheep ( Ovis aries ) reported prevalence of Trichuris ovis (3.67%–58.29%) [22], Trichostrongylus spp. (34.55%) [22], and Strongyloides papillosus (4%) [29].…”
Section: Discussionmentioning
confidence: 99%
“…The coprological results in relation to sex revealed a non significantly higher value in male as compared to female for strongyle, Strongyloides, Trichuris and Moniezia infection. Significantly higher infection in adults as compared to young small ruminants was reported by Dabasa et al (2017) in Bale zone, South Eastern Ethiopia as well as by Rahman et al (2017) in Tangail, Bangladesh. Almost similar percentage of infection in both male and female might be due to similar management practices and same area visited by these animals during grazing.…”
Section: Resultsmentioning
confidence: 72%